Co‐option of developmentally regulated plant SWEET transporters for pathogen nutrition and abiotic stress tolerance. Issue 7 (15th July 2015) - Chandran, Divya; Salunke, Dinakar M.
Abstract Plant sugar will eventually be exported transporter (SWEET) sugar transporters have been implicated in various developmental processes where sugar efflux is essential, including sucrose loading of phloem for long‐distance sugar transport, nectar secretion, embryo and pollen nutrition, and maintenance of sugar homeostasis in plant organs. Notably, these transporters are selectively targeted by pathogens to gain access to host sugars. In most cases, when SWEET function is blocked, the growth and virulence of the pathogen is also reduced. There is growing evidence to suggest that the lifestyle of the pathogen may dictate which SWEET or set of SWEET genes are recruited for pathogen growth and proliferation. Furthermore, SWEET transporters may also play a role in abiotic stress tolerance by enabling plant growth under unfavorable environmental conditions. This review provides an overview of the diverse functions of SWEET proteins in plant development, pathogen nutrition, and abiotic stress tolerance. In addition, utility of the model legume Medicago truncatula as a tool to elucidate SWEET function in diverse host–microbe interactions is discussed. © 2015 IUBMB Life, 67(7):461–471, 2015